A novel SVM option pricing model & an intelligent ATM option straddle trading system - He, Jianxin. (2011)
Options are very popular financial derivatives that allow investors to control their investment risks in the securities market. Determining the theoretical price for an option, or option pricing, is regarded as one of the most important issues in financial research; a number of parametric and nonparametric option pricing approaches have been researched and developed. In this study, we want to propose a novel option pricing model incorporating both the parametric and nonparametric methods. The parametric methods give rough approximations of the current option price, and the nonparametric support vector machine (SVM) focuses on capturing and reducing the error residuals in the approximations to provide more accurate option valuation.